Protective effects of vitamin D3 against D-galactosamine-induced liver injury in rats - Colakoglu, Neriman; Kuloglu, Tuncay; Ozan, Enver; Kocaman, Nevin; Dabak, Durrin Ozlem; Parlak, Gozde (Churchill Livingstone, 2016)
In this study, we examined liver damage induced by D-galactosamine (D-GaIN) and the protective effects of vitamin D-3 in relation to D-GaIN toxicity. Twenty Wistar albino rats were used in this study. The rats were divided into four groups. Group I rats were used as the control group. Group II rats were given a single intraperitoneal injection of D-GaIN. Group III rats were given a single intraperitoneal injection of D-GaIN, intramuscular vitamin D3 for five days. Group IV rats were given intramuscular vitamin D3 for five days. All of rats were euthanized by cervical decapitation on the fifth day of experiment. Upon completion of the experiment, a midsaggital incision was performed, and the livers of all rats were removed and fixed. The livers were processed to perform TUNEL technique and histochemical staining. During the microscope examination, we observed inflamatory cell infiltration, sinusoidal dilatation, and apoptotic bodies due to D-GaIN exposure. In addition, glycogen content of the group II hepatocytes was significantly decreased. Vitamin D3 treatment provided better structural apperance of the livers in group III. TUNEL positive cells were extremly pervasive in the group II livers. The study found group III TUNEL positive cells at a reduced rate in relation to group II due to vitamin D3 treatment. This findings indicate that D-GaIN causes inflamation in the liver. This inflamation triggers the apoptotic process gradually. Vitamin D3 has potency to decrease the severity of D-GaIN-caused structural liver damage. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: D-Galactosamine; Liver injury; Vitamin D-3; Apoptosis; TUNEL; Microscope